Strategi Digital Marketing Rustic Market Forest Tree Untuk Tetap Bertahan dan Berkembang di Tengah Kompetisi Cafe Viral dan Kekinian di Surabaya - Nengrugaya; Agoes Tinus Lis Indrianto (JURNAL ILMIAH EDUNOMIKA, 2026)
The growth development of digital technology and social media has changed how culinary businesses promote their products and connect with customers. In Surabaya, the café industry is now more competitive because many viral and trendy cafés use digital platforms to attract consumers. This situation means businesses need effective digital marketing strategies to survive and grow. Rustic Market Forest Tree is a café that uses social media for promotion, focusing on its nature-theme concept. However, there is still limited research on how marketing strategies help business growth. This study aims to analyze the role of digital marketing in supporting the growth and sustainability of Rustic Market Forest Tree and to identify the strategies used to compete with viral cafés in Surabaya. The research uses a qualitative case study approach. Informants were chosen through purposive sampling and include digital marketing team members, operational staff, and active customers, with a total of 15 participants. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive analysis model. The results show that digital marketing is important for increasing customer engagement, strengthening brand positioning, and encouraging visits through content planning, authentic visual, digital interaction, and combining online and offline branding.